Studentification : students’ perception on houses’ physical condition / Lizawati Abdullah, Ilyana Bazlin Mohd Nor and Norhaslina Jumadi - Abdullah, Lizawati; Mohd Nor, Ilyana Bazlin; Jumadi, Norhaslina (2012)
This paper presents analyses of the student’s housing condition in Seri Iskandar, Perak. The discussion and results provide the information on the factors that influences the student’s choices and also perceptions on the current house’s condition. In this study, data were collected through a quantitative survey. At the end of the study, shows a contradicting result in terms of students’ perception and their current houses condition. This shows that most students chose rent affordability over comfortable living. This research adds to the housing market knowledge from the aspects of student’s housing.